Changing world environment with special reference to small states - Bourne, Compton ([s.n.] [S.l.], 1991)
Identifies some of the major developments and trends in the changing world environment and indicates their possible implications for small states. Reviews features of the world environment such as population and economic growth and distribution, international trade, international finance, the environment and politics. Concludes that small nations need to rethink their economic development policies.